Promoter Methylation of MLH1, PMS2, MSH2 and p16 Is a Phenomenon of Advanced-Stage HCCs - Hinrichsen, Inga (Public Library of Science, 2014)
Epigenetic silencing of tumour suppressor genes has been observed in various cancers. Looking at hepatocellular carcinoma (HCC) specific protein silencing was previously demonstrated to be associated with the Hepatitis C virus (HCV). However, the proposed HCV dependent promoter methylation of DNA mismatch repair (MMR) genes and thereby enhanced progression of hepatocarcinogenesis has been the subject of controversial discussion. We investigated promoter methylation pattern of the MMR genes MLH1, MSH2 and PMS2 as well as the cyclin-dependent kinase inhibitor 2A gene (p16) in 61 well characterized patients with HCCs associated with HCV, Hepatitis B virus infection or alcoholic liver disease. DNA was isolated from formalin-fixed, paraffin-embedded tumour and non-tumour adjacent tissue and analysed by methylation-specific PCR. Moreover, microsatellite analysis was performed in tissues showing methylation in MMR gene promoters. Our data demonstrated that promoter methylation of MLH1, MSH2, PMS2 and p16 is present among all considered HCCs. Hereby, promoter silencing was detectable more frequently in advanced-stage HCCs than in low-stage ones. However, there was no significant correlation between aberrant DNA methylation of MMR genes or p16 and HCV infection in related HCC specimens. In summary, we show that promoter methylation of essential MMR genes and p16 is detectable in HCCs most dominantly in pT3 stage tumour cases. Since loss of MMR proteins was previously described to be not only responsible for tumour development but also for chemotherapy resistance, the knowledge of mechanisms jointly responsible for HCC progression might enable significant improvement of individual HCC therapy in the future.